Interactions of Butyrylcholinesterase with Neuroblastoma-associated Oncoproteins - Baranowska-Kortylewicz, Janina; Kortylewicz, Zbigniew P.; McIntyre, Erin M.; Sharp, John G.; Coulter, Don W. (Current Enzyme Inhibition, 2023)
Background: Emerging data indicate that BCHE, a gene encoding the enzyme butyrylcholinesterase, is a negative prognostic marker in MYCN-amplified neuroblastoma. Levels of butyrylcholinesterase in children newly diagnosed with neuroblastoma are proportional to MYCN amplification and the response to therapy. To better understand the functions of butyrylcholinesterase in neuroblastoma, we examine interactions of this enzyme with several neuroblastoma-associated kinases and provide in depth review of known associations. Methods: BCHE-deleted cells (KO) were produced from MYCN-amplified BE(2)-C cells (WT) by the CRISPR-Cas9 targeted disruption of the BCHE locus. Activation levels of several oncoproteins and the expression of N-Myc in KO were compared to WT cells. N-Myc protein expression, multiplexed detection of relative protein expression and phosphorylation of 71 tyrosine kinases and 17 proteins in the MAPK pathway were assessed using Western immunoblotting and microarrays in exponentially growing untreated cells and in cells exposed to the genotoxic stress. Results: BCHE locus disruption and butyrylcholinesterase deficiency result in the loss of N-Myc protein and a significant deactivation of several kinases associated with the aggressive neuroblastoma phenotype as well as major changes in the phosphorylation of upstream and downstream partners of these kinases. Conclusion: Butyrylcholinesterase appears to contribute to the activation of several pathways in MYCN-amplified cells including FGF-R1, Ltk, TrkB, and Ros1. Deletion of BCHE and ensuing butyrylcholinesterase deficit deactivate these pathways suggesting the role of BChE as a novel druggable target in neuroblastoma therapy.
Keywords: Butyrylcholinesterase